Emotional Intelligence and the Propensity to Cheat: A Survey of Future Accounting Students in Indonesia - Yuniar, Tasya; Hanawati, Hanawati (CV. Publikasi Indonesia, 2024)
This research aims to investigate the relationship between emotional intelligence and the tendency to cheat academically among accounting students in Indonesia. The research variables used consisted of independent variables: Emotional Intelligence (EI) and Dependent variables: Academic cheating tendency in Accounting Students. A quantitative approach was used in this study, with data collected through questionnaires distributed through Snowball sampling using WhatsApp messages to active students of the S1 Accounting study program at several universities in Indonesia (the islands of Sumatra and Java). The total respondents of this study were 224 students who could be processed, totaling 210 students. The convenience sampling technique is applied to sample selection. Data analysis using Structural Equation Modeling (SEM) with the help of SmartPLS 3.0 software. The results showed that emotional intelligence and religiosity had a significant negative effect on academic cheating tendencies. Gender is proven to strengthen the negative effect of emotional intelligence and religiosity on cheating tendencies. In conclusion, increasing emotional intelligence and religiosity, as well as the role of gender, can be important factors in reducing cheating tendencies among accounting students. These findings are significant for the development of accounting education curriculum and policies to improve the integrity and professional ethics of future accountants.